The Relationship between Digital Literacy, Career Guidance, and Students’ Career Planning - Wa Ode Husniah; Maria Ulfa; Amanda Putri Aulia (Universitas Negeri Padang, 2026)
Digital transformation has significantly altered the manner in which students access and interpret career information, thereby increasing the relevance of digital literacy and career guidance for career planning at the secondary education level. This research investigates the relationships among digital literacy, career guidance, and the career-planning tendencies of senior high school students. A quantitative cross-sectional design was employed, involving 150 senior high school students in Baubau City, Indonesia, selected through convenience sampling. Data were collected utilizing a self-report instrument developed based on theoretical frameworks and tested for validity and reliability within this study. Data analysis was performed using multiple linear regression. The findings indicate that digital literacy and career guidance are positively and significantly correlated with students' career planning, both concurrently and independently, with the model accounting for 35.9% of the variance in career planning. These results suggest that students' career planning is linked to their ability to manage digital-based career information and the reflective support provided through school-based career guidance services. This study offers empirical evidence derived from the context of secondary education in Indonesia, demonstrating the relationship between digital literacy and career guidance in fostering students' career-planning orientation.